Monitoring consumption Switzerland: data, background, and use cases - Martin Brown; Matthias R. Fengler; Jonas Huwyler; Winfried Koeniger; Rafael Lalive; Robert Rohrkemper (Swiss Journal of Economics and Statistics, 2023)
Abstract Monitoring Consumption Switzerland is a public–private partnership between the University of St. Gallen and the payment companies Worldline and SIX that processes and publishes payment data on transactions in Switzerland processed by Wordline/SIX in real time. This paper provides background information on this novel source of data and presents their attributes, aggregation and granularity, and their interpretability. The paper presents several use cases that show the strengths of the data, and it alerts future users of the data to possible challenges. The paper also discusses the project's impact and provides an outlook.